2001
DOI: 10.1046/j.1523-1747.2001.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

A Strikingly Constant Ratio Exists Between Langerhans Cells and Other Epidermal Cells in Human Skin. A Stereologic Study Using the Optical Disector Method and the Confocal Laser Scanning Microscope11Presented in part at the International Investigative Dermatology 1998, Cologne, Germany 1998.

Abstract: Langerhans cells play an important part in the immune surveillance of the human epidermis. Therefore, a certain distribution and numerical relationship to other epidermal cells can be expected. To quantify epidermal Langerhans cells population extensive studies have been performed using two-dimensional quantification methods on vertical sections or epidermal sheet preparations. Whereas methods using vertical sections were complicated considerably by the sampling procedure, the dendritic shape, and the suprabas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
69
3
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 39 publications
12
69
3
2
Order By: Relevance
“…LC numbers were determined by counting MHC class II-positive cells with recognizable stellate morphology and normalizing for the number of basal keratinocytes; data are expressed as mean number of LCs/100 keratinocytes (41).…”
Section: Construction Of the Jam-a -/-Transgene And Production Of Jammentioning
confidence: 99%
“…LC numbers were determined by counting MHC class II-positive cells with recognizable stellate morphology and normalizing for the number of basal keratinocytes; data are expressed as mean number of LCs/100 keratinocytes (41).…”
Section: Construction Of the Jam-a -/-Transgene And Production Of Jammentioning
confidence: 99%
“…8,31 It is generally believed that DNA-coated gold particles target APC in the upper layer of the skin where they exist at a very high density. 4,5,[32][33][34][35] Furthermore, local injury by gene gun particle bombardment may induce a local inflammatory environment supporting DC maturation and subsequent T-cell activation. 4,5,[36][37][38] Unexpectedly, after gene gun application, Her2/ neu peptide-specific CD8 þ g-IFN T-cell responses were lower after coadministration of CCL19, despite better tumor protection compared with Her2/neu alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the SDMA chip was removed and we confirmed that there were no wounds on the skin. Bauer et al 33) performed safety studies using stainless steel microneedle arrays in human skin, where transepidermal water loss (TEWL) and redness values were measured. Assembled microneedle arrays induced higher TEWL values than solid microneedle arrays, while resulting in less skin irritation lasting Ͻ2 h. Even in the case of metal microneedles, safety was confirmed and we may state that SDMA is safer than metal microneedles.…”
Section: Discussionmentioning
confidence: 99%